TRPM2 Immunreactivity in Cerebellar Purkinje Cell of Ovariectomised Rats - Gonen, Murat; Atilgan, Remzi (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY